Tapinarof Nanogels as a Promising Therapeutic Approach - Barbara Balogh; Ágota Pető; Pálma Fehér; Zoltán Ujhelyi; Ildikó Bácskay (Pharmaceutics)
Psoriasis is a chronic inflammatory skin disease characterised by increased oxidative stress, the overproliferation of keratinocytes, the accumulation of inflammatory mediators, and skin barrier damage. Although a number of therapeutic options are available, finding long-term treatments that are well-tolerated and patient-friendly treatments remains a challenge. Tapinarof is a new type of aryl hydrocarbon receptor (AhR) modulator that has recently attracted attention as a promising non-steroidal alternative. However, its application may be limited by its poor water solubility and low degree of skin penetration. Nanotechnology-based drug carriers, specially nanogels, offer new opportunities to overcome these limitations by combining the advantages of targeted drug delivery and enhanced skin penetration. Furthermore, nanogel formulations can improve skin hydration and support the restoration of skin barrier function, which are important in the treatment of psoriasis. This review focuses on current and emerging therapeutic approaches, with particular emphasis on the potential of incorporating tapinarof into nanogel formulations as a novel alternative to topical psoriasis treatment.